Diaphanosoma Fischer, 1850 (Crustacea: Cladocera: Sididae) of Lake Turkana (East Africa), with the description of a new species of the genus - Korovchinsky, Nikolai M.; Walsh, Elizabeth J.; Smolak, Radoslav (Zootaxa, 2017)
Diaphanosoma turkanae sp. nov. is described from Lake Turkana (Kenya, East Africa). This species is the second Afrotropical endemic in the order Ctenopoda. It is characterized by a distinctive feature, the presence of an unusually small number of setae on the upper two-segmented antennal branch (exopodite); the proximal segment of the branch always bears three setae while the distal segment bears either six or seven setae. Morphologically the new species is most similar to D. orghidani Negrea, also occurring in Africa and presumably sharing an evolutionary affinity. D. turkanae sp. nov. co-occurs with two other species of the genus, D. lacustris Kořinek and D. excisum Sars, which are briefly described here. Temperate-subtropical species of the genus Diaphanosoma penetrate far south along the Nile River system up to the equatorial and Ethiopian lakes and further southwards, often forming multi-species assemblages.